Investigating the prevalence of psychological disorders among children with diabetes aged 5-12 years old referring to Endocrinology clinic of Mofid Hospital in 2014-2015 - Zahed, Ghazal; Shakiba, Marjan; seifi, kimia (Iranian Journal of Child Neurology, 2018)
As there were a few studies about the mental disorders resulting from diabetes in children, this study aimed at investigating the prevalence of psychological disorders among children. the studied samples included 323 children with diabetes type 1 aged 5-12 years old referring to Endocrinology clinic of Mofid Hospital in 2014-2015. Also, 317 healthy children were considered as control group. The materials used for data analysis were information form and questionnaire CSI-4 filled out by their parents. The filled questionnaires were rated in that day and then analyzed and diagnosed by the Pediatric Psychiatry in order to determine the type and intensity of psychological disorder. Results were analyzed using SPSS 20. T tests, Scheffe post hoc test and Pearson’s correlation test were used for analysis of data. The amounts were significantly different at P<0.05. In terms of Neuro-Evolutionary disorders, Attention-deficit (ADD), hyperactivity (HD) and Attention-deficit hyperactivity disorders (ADHD) in children with diabetes were significantly higher than those in healthy children (P=0.001). Intense/ fundamental Depressive disorders were higher in diabetic children (P=0.001). In terms of anxiety disorder, a specific phobia and panic was significantly higher in diabetic children (P=0.005). In terms of aggressive behaviors, diabetic children were more disobedient and stubborn than the others. this study showed that prevalence of psychological disorders among diabetic children was higher than the others. As psychological disorders will effect on the life quality of children, improvement of life quality of diabetic children and adolescents, on-time diagnosis and treatment of psychological disorders in these patients seems essential